Efeitos dos programas de luz sobre o desempenho, rendimentos de abate, aspectos econômicos e resposta imunologica em frangos de corte. - Douglas Teixeira Moraes (2006)
To evaluate the effect of different lighting programs on performance, feed intake at each six hours, economic aspects, carcass characteristics and antibodies production to Newcastle disease of broiler chickens an experiment was conducted with 840 young males chicks of the Cobb-500 lineage. The treatments defined according to the photoperiod were: 23L 23 hours of light and 1 hour of darkness from 1 to 45 days old; CRES 23 hours of light from 1 to 7 days old, without artificial light during the 8and 21 days old, 14 hours of light from 22 to 28 days old, 18 hours of light from 29 to 35 days old and 23 hours of light from 35 to the 45 days old; 16L 16 hours of light from 1 to 45 days old and the NAT program, without artificial light during all the raising period. The poultry was located in an experimental poultry house, 11,60 birds for m2. The lighting intensity at the birds level was of 20 lux during all raising period that was from 1 to 45 days of age. The rations used were the same and offered at pleasure. The statistical design was the complete randomized divided in four treatments with six repetitions of 35 birds each. Analysis of variance with mean separation was made using SNK´s multiple range test forperformance, carcass characteristics, economic aspects and immunological response. Broiler chickens of CRES lighting program presented higher body weight (p<0,05) than birds of the others lighting programs that were similar between then (p>0,05). The feed intake of the birds of the CRES lighting program was higher than the birds of the 23L and NAT (p<0,05) and similar to the 16L treatment (p>0,05). Feedconversion was not observed differences between treatments (p>0,05). The livability was higher in birds of the NAT lighting program than the 23L lighting program (p<0,05) and similar to the others treatments (p>0,05). Feed intake during 24 hours period was not observed differences between treatments at 27 days of age (p>0,05). Feed intake during 24 hours period at 34 days of age was higher in the 16L treatment than the others treatments (p<0,05) that were similar between then (p>0,05). The carcass, foot, head, abdominal fat, liver, heart and gut yield were not observed differences between treatments (p>0,05). The birds of the 23L lighting program presented breast muscle higher than the others treatments (p<0,05). The cost of the broiler kilogram was not observed differences between treatments (p>0,05). The antibody levels against Newcastle disease were not observed differences between treatments (p>0,05).